Etiologies and Management of Aseptic Meningitis in Patients Admitted to an Internal Medicine Department. Issue 2 (January 2016) - Jarrin, Irène; Sellier, Pierre; Lopes, Amanda; Morgand, Marjolaine; Makovec, Tamara; Delcey, Veronique; Champion, Karine; Simoneau, Guy; Green, Andrew; Mouly, Stéphane; Bergmann, Jean-François; Lloret-Linares, Célia
Abstract : Abstract: Several studies have focused on the clinical and biological characteristics of meningitis in order to distinguish between bacterial and viral meningitis in the emergency setting. However, little is known about the etiologies and outcomes of aseptic meningitis in patients admitted to Internal Medicine. The aim of the study is to describe the etiologies, characteristics, and outcomes of aseptic meningitis with or without encephalitis in adults admitted to an Internal Medicine Department. A retrospective cohort study was conducted in the Internal Medicine Department of the Lariboisière Hospital in Paris, France, from January 2009 to December 2011. Clinical and biological characteristics of aseptic meningitis were recorded. These included cerebrospinal fluid analysis, results of polymerase chain reaction testing, final diagnoses, and therapeutic management. The cohort included 180 patients fulfilling the criteria for aseptic meningitis with (n = 56) or without (n = 124) encephalitis. A definitive etiological diagnosis was established in 83 of the 180 cases. Of the cases with a definitive diagnosis, 73 were due to infectious agents, mainly enteroviruses, Herpes Simplex Virus 2, and Varicella Zoster Virus (43.4%, 16.8%, and 14.5% respectively). Inflammatory diseases were diagnosed in 7 cases. Among the 97 cases without definitive diagnoses, 26 (26.8%) remained free of treatment throughout their management whereas antiviral or antibiotic therapy was initiated in the emergency department for the remaining 71 patients. The treatment was discontinued in only 10 patients deemed to have viral meningitis upon admission to Internal Medicine. The prevalence of inflammatory diseases among patients admitted to internal medicine for aseptic meningitis is not rare (4% of overall aseptic meningitis). The PCR upon admission to the emergency department is obviously of major importance for the prompt optimization of therapy and management. However, meningitis due to viral agents or inflammatory diseases could also be distinguished according to several clinical and biological characteristics highlighted in this retrospective study. As recommendations are now available concerning the prescriptions of antiviral agents in viral meningitis, better therapeutic management is expected in the future.